2015
DOI: 10.1177/1087057114551519
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic-Based Strategies for Anti-Parasite Drug Discovery

Abstract: Metabolomics-based studies are proving of great utility in the analysis of modes of action (MOAs) and resistance mechanisms of drugs in parasitic protozoa. They have helped to determine the MOA of eflornithine, half of the gold standard combination therapy in use against human African trypanosomiasis (HAT), as well as the mechanism of resistance to this drug. In Leishmania, metabolomics has also given insight into the MOA of miltefosine, an alkylphospholipid. Several studies on antimony resistance in Leishmani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 98 publications
0
47
0
Order By: Relevance
“…To do this, we plan to use a combined approach of advanced, high-resolution microscopic imaging and metabolomics. Metabolomics should provide an effective way of establishing which biochemical pathways in H. contortus are affected by individual compounds, and will be highly complementary to transcriptomic and proteomic analyses (reviewed by Mikami et al 2012;Vincent and Barrett 2015). Our goal is to study individual phenotypes of various developmental stages of the parasites during treatment with particular drug candidates (different dosages and time points), and quantitatively assess their metabolic profiles compared with untreated controls, which will enable us to verify that chemical knock-down relates specifically to particular pathways or metabolic chokepoints inferred from the druggable genome (cf.…”
Section: Proposed Hit-to-lead Phasementioning
confidence: 99%
“…To do this, we plan to use a combined approach of advanced, high-resolution microscopic imaging and metabolomics. Metabolomics should provide an effective way of establishing which biochemical pathways in H. contortus are affected by individual compounds, and will be highly complementary to transcriptomic and proteomic analyses (reviewed by Mikami et al 2012;Vincent and Barrett 2015). Our goal is to study individual phenotypes of various developmental stages of the parasites during treatment with particular drug candidates (different dosages and time points), and quantitatively assess their metabolic profiles compared with untreated controls, which will enable us to verify that chemical knock-down relates specifically to particular pathways or metabolic chokepoints inferred from the druggable genome (cf.…”
Section: Proposed Hit-to-lead Phasementioning
confidence: 99%
“…(Husain et al 2010;Jeelani et al 2012) have been conducted extensively. These comprehensive studies of metabolomic in host-parasite interaction and disease aetiology will greatly contribute to the discovery of metabolomic-based antiparasite drug (Vincent & Barrett 2015) to facilitate the management of disease treatment and prevention that will benefit the aquaculture industry.…”
Section: Parasite Infectionmentioning
confidence: 99%
“…CE coupled to a TOF mass spectrometer provides a powerful tool capable to detect a wide range of polar and ionic compounds discriminating isotopes . A few review papers have been published that highlight the technical developments and various applications of CE–MS‐based metabolomics and recently, a review has been published that describes the strategies followed in metabolomics studies of parasites . Regarding Leishmania , other authors have reported only metabolomics studies by LC–MS and GC–MS .…”
Section: Introductionmentioning
confidence: 99%